Abruptio placentae: impact of early treatment on maternal and fetal outcomes - Mehta, Shikha P.; Deshmukh, Prasad Y.; Bawa, Amarjeet K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Haemorrhage is the leading cause for maternal mortality in India as well as the world. Abruptio placenta is the second most common cause of antepartum haemorrhage and it is associated with sudden, severe and devastating maternal and fetal complications. The main objective of this study is to study the impact of early treatment on maternal and fetal outcomes. Methods: This single center retrospective study includes all patients admitted at Lokmanya Tilak Municipal General Hospital, a tertiary referral hospital, diagnosed to have abruptio placenta (grade II and grade III) from 01 July 2019 to 31 December 2019. In this study a total of 48 cases were included and data regarding time duration between onset of symptoms and initiation of treatment, clinical course and maternal and fetal outcomes was noted. Results: A total of 5059 deliveries occurred over six months. The incidence of placental abruption was found to be 0.94%. Patients receiving early care (30 cases, 62.5%) were found to have significantly better maternal outcomes (p=0.006, Chi square test) as well as fetal outcomes (p=0.007, Fischer’s exact test) than patients who received delayed care (18 cases, 37.5%). Conclusions: Abruptio placentae is an obstetric emergency and early diagnosis as well as initiation of treatment plays an important role in curbing complications. Strengthening of peripheral centers, availability of multi-disciplinary approach and educating health care staff as well as patients form the cornerstones of improved maternal and fetal outcomes.